Algoritma pendaraban nombor perpuluhan dari perspektif pelajar Tingkatan Satu - Md. Yunus, Aida Suraya (Universiti Putra Malaysia Press, 2001)
This study discusses the algorithms in multiplication involving decimal numbers from the perspectives of Form One students. Qualitative data gathered through two clinical interview sessions in a case study conducted within the constructivist theory were collected from six Form One students of different mathematical abilities, based on their mathematics performance in the Ujian Penilaian Sekolah Rendah. Studies based on Constructivisme focus on describing students' understanding from their own perspectives. Seven algorithms used by students in multiplying decimal numbers were identified. Identification of students' algorithms has implications towards the teaching and learning activities and forms a basis in planning teaching strategies of multiplication involving decimals for mathematics educators.